Efeitos da desconexão hipotalâmica aguda e crônica sobre as respostas pressoras induzidas pela injeção central de salina hipertônica, carbacol e angiotensina II em ratos - Rodrigues, Lilia Simone Urzedo (2005)
Several anatomical and functional studies have demonstrated that the paraventricular nucleus of the hypothalamus (PVN) constitutes a neuroendocrine center. The PVN is intimately related to the regulation of the sympathetic nerve activity and vasopressin secretion. Intracerebroventricular injections of angiotensin II (ANG II), carbachol and hypertonic saline induce an increase in arterial pressure by sympathetic activation and/or vasopressin secretion. Furthermore, it was demonstrated that hypothalamic disconnection (HD) caudal to PVN, performed by way of a knife-cut into the hypothalamus using a microknife of bayonet shape, produced a decrease in basal arterial pressure, suggesting that the fibers interrupted by this HD, probably from PVN, are part of a neural circuitry responsible for tonic maintenance of the arterial pressure. Therefore, the aims of this study were to determine, in conscious rats, the effects of HD caudal to PVN (HD-C) on: a) the pressor response induced by intracerebroventricular injection of ANG II, carbachol and hypertonic saline, b) on the baroreflex and chemoreflex, c) on urinary excretion after 24 h of water deprivation. Male Holtzman rats (280-320 g) were submitted to sham-HD or acute (1 day) or chronic (15 days) HD caudal to PVN (HD-C) performed with a microknife of bayonet shape (radius = 1 mm, height = 2 mm) stereotaxically placed, positioned 1.5 mm caudal to the bregma, lowered along the midline down to the inner surface of the sphenoid and the cut as achieved by rotating it 90° left e 90° right. In sham-HD no rotation was performed. After the HD, a cannula was implanted into the lateral ventricle. Femoral vein and arterial catheters were introduced after the surgery to implant the cannula into LV (acute group) or 14 days after HD (chronic group). Rats submitted to acute HD-C did not have changes in basal mean arterial pressure (MAP), but had an increase in basal heart rate (HR), (423 ± 17 bpm) compared to sham HD rats (346 ± 8 bpm). Chronic HD did not change basal levels of MAP or HR. Baroreflex was also not changed by acute or chronic HD-C. In regard to chemoreflex, although the peak of the pressor and the bradycardic response to chemoreflex activation were not changed by acute or chronic HD-C, the duration of the pressor response was reduced in rats submitted to chronic HD-C (18±2 s) compared to sham-HD (28±3 s). The pressor response induced by intracerebroventricular (icv) injection of hypertonic saline was reduced by acute or chronic HD-C (7±3 and 21±2 mmHg vs. sham-HD: 19±4 and 36±5 mmHg, respectively). The acute or chronic HD-C also reduced the pressor response induced by icv injection of carbachol (12±3 and 21±3 mmHg vs. sham-HD: 32±4 and 35±4 mmHg, respectively) and ANG II (12±3 and 12±2 mmHg vs. sham-HD: 23±2 and 22±2 mmHg, respectively). In the 24 h water deprivation experiments, we observed a higher potassium excretion in rats with acute HD-C (DH-C: 1278±248 µEq/24 h vs sham-HD: 682±87 µEq/24 h) or chronic (DH-C: 1480±281 µEq/24 h vs sham-HD: 787±75 µEq/24 h), respectively. In chronic HD-C rats the urine volume excreted in 24 h of water deprivation was greater than the one observed in sham-HD rats (DH-C: 19±2 ml vs sham-HD: 9±0,4 ml), while the urinary volume excreted in 24 h of water deprivation in rats submitted to acute HD-C were not different from sham-HD rats. HD-C animals had polidipsia from the 6th 8th day after the HD-C, which was maintained until the last day of the experiment (14 or 17th day). These results suggest that the pressor responses induced by central injections of ANG II, carbachol and hypertonic saline, but not the baro and chemoreflex, depend on the neural pathways injured by HD-C. It is possible that the lesser pressor responses induced by central injections of these substances in HD-C rats are due to a lesser activation of sympathetic activity and/or vasopressin secretion. It is also possible that the lesser vasopressin secretion in HD-C rats is responsible for the polidipsia observed in these animals.